Understanding business markets : interation, relationships and networks (London : The Dryden Press, 1997)
Interaction and relationships in business markets. Business markets as networks. Developing marketing strategy. Developing purchasing strategy. Technology and networks.
Keywords: Industrial marketing; Business markets; Industrial marketing